Quantitative Analysis of the Economic Risk of Sugarcane Cultivation for Bioethanol Production: A Case Study in Brazil - Simoes, Danilo [UNESP]; Cervi, Ricardo Ghantous [UNESP]; Batistela, Gislaine Cristina [UNESP] (North Carolina State Univ Dept Wood & Paper Sci, 2018)
The management of variables with uncertainties in stochastic cash flow models related to capital investments in energy crops projects allows, in addition to risk measurement, the adoption of proactive measures that can assure the generation of value to the project. This study analyzes the economic feasibility of sugarcane cultivation for bioethanol production from sugarcane molasses, under technical and economic uncertainty. The analysis characterizes sugarcane productivity, capital investment, production costs, and costs of cutting, loading, and transport, considered as stochastic variables. For this, the uncertainty was propagated through Latin hypercube sampling. Sensitivity analysis was also performed to assess the impact of these variables. The results indicated that the productivity of the crop and the sugarcane price in the conveyor belt are determinant to guarantee the economic value of the investment project. There is a high probability of achieving positive NPV (net present value), in addition, MIRR (modified internal rate of return) is 5% higher than MARR (minimum acceptable rate of return).
Keywords: Uncertainty; Renewable energy; NPV; Cost estimate; Stochastic analysis